Identification of key genes and biological pathways in different parts of yak oviduct based on transcriptome analysis - Jian Zhang; Jian Zhang; Yangyang Pan; Yangyang Pan; Ling Zhao; Ling Zhao; Tian Zhao; Tian Zhao; Sijiu Yu; Sijiu Yu; Yan Cui; Yan Cui (Frontiers in Veterinary Science, 2022)
The oviduct consists of three parts: the infundibulum (In), ampulla (Am), and isthmus (Is). These have the same histological structure, but different physiological functions. In this study, transcriptomics was used to analyze mRNA in these three parts of yak oviduct. The results showed that there were 325 up-regulated genes and 282 down-regulated genes in the infundibulum and ampulla. Moreover, there were 234 up-regulated genes and 776 down-regulated genes in the isthmus and ampulla, as well as 873 up-regulated genes and 297 down-regulated genes in the infundibulum and isthmus. The expression of C3 in the infundibulum was significantly higher than that in the ampulla and isthmus. The expression of FAU in the isthmus was significantly lower than that in the ampulla and infundibulum, and the expression of EEF1A1 in the ampulla was significantly higher than that in the ampulla and infundibulum. When the infundibulum was compared with the ampulla and isthmus, it was found that the up-regulated genes were enriched in the lysosome, phagosome, staphylococcus aureus infection, and leishmaniasis pathway. When the isthmus was compared with the ampulla and infundibulum, the up-regulated genes were present in the apoptosis pathway, oxidative phosphorylation, and viral myocarditis pathway. When the isthmus was compared with the infundibulum and ampulla, the down-regulated pathways were protein processing in the endoplasmic reticulum and the endocytosis. The Epstein–Barr virus infection pathway was up-regulated according to a comparison of the isthmus and infundibulum and was down-regulated based on a comparison of the isthmus and ampulla. Transcriptional misregulation in the Middle East pathway was up-regulated based on a comparison of the isthmus and ampulla and was down-regulated based on a comparison of the isthmus and infundibulum. ERBB2, JUP, CTNND1, and KRT7 were defined as the hub genes of the yak oviduct. The results of this study provide sufficient omics data for yak fertilization, which is also of great significance to altitude medicine.